Loyalitas Merek Milo Ditinjau dari Kualitas Produk dan Brand Image - Ella Anastasya Sinambela; Rahayu Mardikaningsih (Universitas Nusantara PGRI Kediri, 2022)
One of the roles of marketing management is to win the market competition. This situation will make the company's sales increase and ultimately provide profits for the company. In addition, market competition also occurs to attract consumers' attention. The marketing strategy implemented by the company's management aims to build brand loyalty from consumers. Therefore, marketing managers improve the forming aspects of brand loyalty. This study aims to determine the role of product quality and brand image to build brand loyalty. The method applied is a quantitative method, then the data is processed using the SPSS V.25 application. The population used is the consumer of Milo brand milk in the city of Surabaya. The sampling technique was accidential sampling with a total of 100 respondents. This study shows that brand loyalty is influenced by product quality and brand image.